Sosialisasi Kecakapan Pengelolaan Keuangan Sebagai Bekal Masa Depan Remaja - Siti Fathiyatus Sholihah (MENARA RIAU, 2023)
Getting married is the dream of every individual. However, most of couples still lack financial knowledge. Mismanagement of finance is one of the reasons for the increase in divorce cases. The aim of this program is to reduce the divorce rate by providing socialization that discusses financial problems to teenagers. Therefore, the researcher held this program in Karangbangun, Jumapolo, Karanganyar. There were 20 youths as participants that consist of 12 boys and 8 girls which was held on Sunday, 19 February 2023 at the Karangbangun Village Hall. This program is carried out by giving lectures, filling out questionnaires, and asking questions. After carrying out this socialization, participants are expected to be able to prioritize basic needs, overcome future financial problems in the household, and understand the right type of investment.